2020
DOI: 10.3390/rs12213473
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Desert Dust Indirect Effects on Cloud Microphysics through a Cloud Nucleation Scheme: A Case Study over the Western Mediterranean

Abstract: In this study, the performance and characteristics of the advanced cloud nucleation scheme of Fountoukis and Nenes, embedded in the fully coupled Weather Research and Forecasting/Chemistry (WRF/Chem) model, are investigated. Furthermore, the impact of dust particles on the distribution of the cloud condensation nuclei (CCN) and the way they modify the pattern of the precipitation are also examined. For the simulation of dust particle concentration, the Georgia Tech Goddard Global Ozone Chemistry Aerosol Radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 102 publications
(116 reference statements)
0
15
0
Order By: Relevance
“…Comparisons with observational data have indicated that the model's performance concerning the simulation of the precipitation processes has been in general improved as statistical biases and errors become limited. The benefits of the abovementioned cloud nucleation scheme on the spatiotemporal distribution of precipitation can be verified even for days after the dust event and for locations away from it (Tsarpalis et al, 2020).…”
Section: Thesis Contribution Beyond the State-of-the-artmentioning
confidence: 92%
See 4 more Smart Citations
“…Comparisons with observational data have indicated that the model's performance concerning the simulation of the precipitation processes has been in general improved as statistical biases and errors become limited. The benefits of the abovementioned cloud nucleation scheme on the spatiotemporal distribution of precipitation can be verified even for days after the dust event and for locations away from it (Tsarpalis et al, 2020).…”
Section: Thesis Contribution Beyond the State-of-the-artmentioning
confidence: 92%
“…Aerosols affect directly the radiation budget (direct aerosol effect) (Myhre et al, 2003;Ramanathan et al, 2007;Solomos et al, 2011;Spyrou et al, 2010) Furthermore, they impact the biochemical cycles of both terrestrial and marine ecosystems and affect human health (Dockery, 1994;Goudie, 2014;Herut et al, 2002;Mahowald et al, 2008;Mitsakou et al, 2008). Moreover, they alter the hydrological cycle, the cloud formation (indirect aerosol effect) and the precipitation pattern (Albrecht, 1989;DeMott et al, 2010;Sassen et al, 2003;Solomos et al, 2011;Tsarpalis et al, 2020;Twomey, 1977). Thus, the definition of the concentration and the characteristics of the aerosols in the atmosphere is fundamental for the studying of their impact on the cloud formation and the precipitation mechanisms.…”
Section: περίληψηmentioning
confidence: 99%
See 3 more Smart Citations